Cooperative Script Model for Fifth-Grade Reading Comprehension: Model Cooperative Script untuk Pemahaman Membaca Siswa Kelas V - Salmiah, Juni; Guswita, Reni; Abdulah (Universitas Muhammadiyah Sidoarjo, 2025)
Background (general): Reading comprehension is a key skill in elementary education, yet many students still struggle to understand texts effectively. Background (specific): In Grade V at SDN 106/II Sungai Binjai, difficulties such as limited vocabulary, low comprehension, and weak ability to answer text-based questions were observed. Knowledge Gap: Previous studies have shown positive outcomes of the Cooperative Script model in various contexts, but limited research has focused specifically on its application in Grade V Indonesian language learning. Aims: This study aimed to improve students’ reading comprehension through the Cooperative Script model within a Classroom Action Research framework. Results: Across two cycles, findings revealed improvements in teacher performance (from 77.78% to 94.44%), student activeness (from 61.10% to 100%), and comprehension mastery (from 33.3% to 72.2%). Novelty: This research demonstrates the applicability of Cooperative Script in elementary-level Indonesian language comprehension, filling a contextual gap in existing literature. Implications: The study suggests Cooperative Script can be integrated into primary curriculum design to foster active, collaborative, and deeper comprehension learning. Highlight Cooperative Script improved teacher engagement, student activity, and comprehension mastery Reading comprehension achievement increased significantly across two research cycles Cooperative Script fosters collaborative and active learning in elementary classrooms Keyword Cooperative Script, Reading Comprehension, Elementary Students, Collaborative Learning, Indonesian Language